Analisis Struktur Ruang dan Perkembangan Kota di Kecamatan Wonosari Kabupaten Gunung Kidul - Muhammad Irvan Aditiya (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2022)
The development of the city is related to how the spatial structure of the city is formed, every city development becomes forming in a space in representing the use of space.. The purpose of this study was to obtain the results of spatial structure analysis and urban development in Wonosari District, Gunung Kidul Regency. This research focuses on the aspect of Wonosari District which is based on the spatial structure. The results of this study are that the physical conditions of the environment and public facilities are interrelated in the formation of the spatial structure, wherein 14 villages there is the highest number of public facilities of 28 and the lowest of 5 facilities, with a range of 5.75 so that it gets 4 classifications of the Wonosari District spatial hierarchy. A total of 2 villages become the city service center, 1 village is the city service center, 2 villages are supporting the city service center and 9 other villages are supporting the city service center. Supporting public facilities are also influenced by the physical condition of the area such as flat slopes, groundwater hydrology, and community land use.